Utilizing ChatGPT on Designing English Language Teaching (ELT) Materials in Indonesia: Opportunities and Challenges - Susanto, Dias Andris; Priyolistiyanto, Andi; Pinandhita, Fitra; K.A, A.B. Prabowo; Bimo, Djoko Sri (Soegijapranata Catholic University, 2024)
This study aims to examine the impact of artificial intelligence (AI) on pragmatic English language teaching in universities. The scope of the study is limited to the opportunities and challenges of English language teaching. This study was carried out using a mixed method of conducting surveys and in-depth interviews. A questionnaire link using Google Forms from Spreadsheet was sent to 6 English lecturers via WhatsApp group and personal contact. The study sample consisted of 6 English lecturers from state and private universities in Central Java. Observation, questionnaire analysis, and interview transcripts show that the emergence of artificial intelligence (AI) technology has created opportunities and challenges to teaching and learning English. AI has transformed English language teaching in higher education. The findings and discussion elaborate some novelties of this study; 1) the profile of utilizing ChatGPT in pragmatics ELT teaching, portrays that ChatGPT roles in teaching scenarios play 3 major sessions, like; designing creative and innovative pragmatics teaching materials, setting up the midterm test of pragmatics project, and lastly, assessing and evaluating the pragmatics final test project. 2) The opportunities of using ChatGPT for lecturers, ChatGPT is one of the most sophisticated AI tools available today, and it can write nearly anything that an instructor wants it to. ChatGPT can help lecturers with a variety of tasks, such as creating course outlines, student progress reports, test and quiz questions, and grading rubrics; developing more inclusive and accessible learning activities; interacting with students and their families; and contributing text for websites or bulletin boards to maintain a connection between students and their families. 3) The challenges of applying ChatGPT for lecturers; ChatGPT can provide immediate responses to student questions, ChatGPT can adapt to individual student needs, ChatGPT can increase accessibility and inclusivity by providing language support for students with diverse learning needs, ChatGPT can serve as a valuable tool for language practice and strengthening, ChatGPT can encourage active learning by encouraging students to ask questions, engage in discussions, and seek clarification on challenging concepts, Integrating ChatGPT into language teaching can inspire innovative teaching approaches, such as blended learning models, flipped classrooms, and gamified learning experiences, that leverage technology to improve student learning outcomes